Determinan Keputusan Invetasi Reksa Dana Melalui Aplikasi Online: (Studi Kasus Pada Kelompok Studi Pasar Modal Universitas Hindu Indonesia) - Amurwabumi, Ni Putu Nandini Semara; Sumadi, Ni Komang; Kusumawati, Ni Putu Ayu (UNHI Press, 2025)
Research conducted at the University Capital Market of Indonesian Hinduism evaluates the impact of attitudes, subjective norms, and behavioral control on the interest and decisions of investing in mutual funds through online applications. The study, utilizing primary data from 39 active members of KSPM UNHI and employing the PLS test, finds that attitudes and behavioral control do not significantly affect interest in investing. However, subjective norms positively influence both interest and decisions to invest in mutual funds online, with interest directly impacting investment decisions. The results suggest a need for increased socialization, education, and understanding of online application use for mutual fund investment, alongside further exploration of individual investment determinants.